2018
DOI: 10.1002/brb3.968
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury after pulsed methylprednisolone therapy in multiple sclerosis patients

Abstract: ObjectivesHigh‐dose pulsed methylprednisolone‐related liver injury cases have been reported in the literature, but a prospective study in patients with multiple sclerosis (MS) has never been performed. The aim of this study was to evaluate the prevalence and severity of liver injury in patients with MS after pulsed methylprednisolone therapy.MethodsWe performed a prospective observational single‐center study on patients with MS treated with i.v. methylprednisolone 1,000 mg/day for 5 days. We tested the liver f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 47 publications
(96 reference statements)
0
25
0
3
Order By: Relevance
“…To date a limited number of cases of methylprednisolone-induced hepatotoxicity had been described 7 10–24. We report an idiosyncratic toxic hepatitis from high-dose methylprednisolone in a 16-year-old girl.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…To date a limited number of cases of methylprednisolone-induced hepatotoxicity had been described 7 10–24. We report an idiosyncratic toxic hepatitis from high-dose methylprednisolone in a 16-year-old girl.…”
Section: Discussionmentioning
confidence: 91%
“…Nociti et al 23 performed a prospective observational study on patients with MS after methylprednisolone therapy and observed a prevalence of 8.6% of liver injury. They described six cases of patients with severe liver injury after pulsed methylprednisolone therapy; five of them were female and three of them with a probable autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of differential diagnosis, AIH must be distinguished from a drug-induced liver injury caused by AI, which can be confirmed by re-exposure 83. As a supplement, liver injury after pulsed methylprednisolone therapy in PwMS with RRMS has been observed both as acute drug-induced liver injury and as AIH 84,85. AIH was observed in 40 reported cases in PwMS receiving disease-modifying drug therapy 86.…”
Section: “Surprises” In the Repertoire Of Unwanted Secondary Autoimmumentioning
confidence: 99%